2011
DOI: 10.1242/jcs.087700
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein dynamics within the septate junction reveals a highly stable core protein complex that does not include the basolateral polarity protein Discs large

Abstract: Barrier junctions prevent pathogen invasion and restrict paracellular leakage across epithelial sheets. To understand how one barrier junction, the septate junction (SJ), is regulated in vivo, we used fluorescence recovery after photobleaching (FRAP) to examine SJ protein dynamics in Drosophila. Most SJ-associated proteins, including Coracle, Neurexin IV and Nervana 2, displayed similar, extremely immobile kinetics. Loss of any of these components resulted in dramatically increased mobility of all others, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
113
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 61 publications
(94 reference statements)
11
113
0
1
Order By: Relevance
“…As Gliotactin is an important constituent of tricellular septate junctions and Neuroglian is a core component of general septate junctions (Genova and Fehon, 2003;Oshima and Fehon, 2011;Schulte et al, 2003), this corroborates the pivotal function of the EGF receptor in organizing septate junctions in the SPG. A possible link between EGF receptor activation and septate junction formation might either stem from a direct transcriptional activation or it could be due to changes in alternative splicing (Edenfeld et al, 2006;Oshima and Fehon, 2011). Cell type-specific splicing of neurexinIV, encoding another core component of septate junctions, is brought about by the splicing factor How, the activity of which can be regulated through phosphorylation by Raf/MAP kinase (Nir et al, 2012;Rodrigues et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As Gliotactin is an important constituent of tricellular septate junctions and Neuroglian is a core component of general septate junctions (Genova and Fehon, 2003;Oshima and Fehon, 2011;Schulte et al, 2003), this corroborates the pivotal function of the EGF receptor in organizing septate junctions in the SPG. A possible link between EGF receptor activation and septate junction formation might either stem from a direct transcriptional activation or it could be due to changes in alternative splicing (Edenfeld et al, 2006;Oshima and Fehon, 2011). Cell type-specific splicing of neurexinIV, encoding another core component of septate junctions, is brought about by the splicing factor How, the activity of which can be regulated through phosphorylation by Raf/MAP kinase (Nir et al, 2012;Rodrigues et al, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Likewise, it was shown that expression of Neuroglian is dramatically reduced in egfr mutants (Sepp and Auld, 2003b). As Gliotactin is an important constituent of tricellular septate junctions and Neuroglian is a core component of general septate junctions (Genova and Fehon, 2003;Oshima and Fehon, 2011;Schulte et al, 2003), this corroborates the pivotal function of the EGF receptor in organizing septate junctions in the SPG. A possible link between EGF receptor activation and septate junction formation might either stem from a direct transcriptional activation or it could be due to changes in alternative splicing (Edenfeld et al, 2006;Oshima and Fehon, 2011).…”
Section: Discussionmentioning
confidence: 55%
“…Similar to mutations in other genes encoding core SJ components (Oshima and Fehon, 2011) (Fig. 5A,B; supplementary material Fig.…”
Section: Research Articlesupporting
confidence: 55%
“…Behr et al, 2003;Genova and Fehon, 2003;Paul et al, 2003;Faivre-Sarrailh et al, 2004;Tiklová et al, 2010). Fluorescence recovery after photobleaching (FRAP) experiments have revealed that SJ proteins are essentially fixed in the membrane by stage 14 of embryogenesis (Laval et al, 2008;Oshima and Fehon, 2011). Mutations in any core SJ gene increases the mobility of other SJ proteins at stage 14, further demonstrating the highly stable and interdependent nature of the SJ complex.…”
mentioning
confidence: 99%
“…We found that the core septate junction components Neurexin-IV (Nrx-IV) and Coracle (Cora) (Oshima and Fehon, 2011) both localized around the germline throughout spermatogenesis (Fig. 7A).…”
Section: Chic Is Required In the Soma For Fertilitymentioning
confidence: 99%